2006
DOI: 10.1007/s10535-006-0100-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chilling on growth and nitrogen assimilation in Azolla caroliniana

Abstract: Azolla caroliniana was exposed to 5 °C in darkness for 1, 2, 3, 5 or 7 d and then recovered for 7 d. Plants previously chilled for 2 or 3 d exhibited higher growth rates when transferred to normal temperature than either the control plants or those previously chilled for 5 or 7 d. Increased plant growth may be related to increased contents of chlorophyll, sucrose, and reducing sugars, due to increased photosynthetic capacity. In another experiment Azolla plants were chilled at 5 °C for 7 d and then transferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Many authors reported that Azolla plants grew significantly better in presence of nitrate in comparison to those entirely dependent upon symbiotically fixed nitrogen (Rai and Rai 2003;Mostafa and Hassan 2006). In our study, addition of different concentrations of NaCl (0, 50, 100, and 150 mM) for 5, 10, and 15 days in presence of 4 mM nitrate exhibited a reduction in biomass and RGR, and this reduction resulted in an increase in DT over the control.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Many authors reported that Azolla plants grew significantly better in presence of nitrate in comparison to those entirely dependent upon symbiotically fixed nitrogen (Rai and Rai 2003;Mostafa and Hassan 2006). In our study, addition of different concentrations of NaCl (0, 50, 100, and 150 mM) for 5, 10, and 15 days in presence of 4 mM nitrate exhibited a reduction in biomass and RGR, and this reduction resulted in an increase in DT over the control.…”
Section: Discussionsupporting
confidence: 49%
“…in the presence of nitrate, the contribution of cyanobacterial fixed nitrogen is then negligible (Reddy et al 1989;Rai and Abraham 1995). In contrary, Azolla-Anabaena relationship is tolerant to repression by combined nitrogen (Peters 1978;Mostafa and Hassan 2006). It has been reported reduction in the NaCl-induced growth inhibition of cyanobacteria by nitrate and the reason given is that NO À 3 and Na ' share a common transport system (Reddy et al 1989;Rai and Tiwari 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cold temperature stress (0-10 o C) has a broad spectrum effects on cellular components including plasma membranes, chloroplasts and mitochondria as well as physiological and biochemical processes of plants Hassan, 2006 andYin et al, 2009). Moreover, low temperature has an inhibitory effect on uptake of mineral elements such as P, K, Ca, Mg, Fe, Zn and B and their allocation between different plant organs, and finally depress the growth (Taspinar et al, 2009 andNxawe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%